IMF Glossary : English-French-Spanish, Seventh edition. (International Monetary Fund, 2007)
This seventh, revised edition of the IMF Glossary: English-French-Spanish contains approximately 4,000 records that are believed to be the most useful to translators dealing with IMF material. The main body of the Glossary consists of terms, phraseological units, and institutional titles covering areas such as macroeconomics, money and banking, public finance, taxation, balance of payments, statistics, accounting, and economic development. It contains terminology relating to the IMF's organization and operations, as well as from the Articles of Agreement, By-Laws, Rules and Regulations, and other major IMF publications. Since the Glossary is concept-based, synonyms are consolidated into one single entry. Cross- references refer to the main entry under which the various synonyms are listed ("see") and also draw the user's attention to terms that are related but not synonyms ("see also"). Currency units of countries and monetary unions, an IMF organizational chart in the three languages, and color-coded French and Spanish indexes are provided in appendixes.